2009
DOI: 10.1007/s11090-009-9181-3
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Azo Dye Acid Red 88 by Gas Phase Dielectric Barrier Discharges

Abstract: The degradation of an azo dye, acid red 88 (AR88) in aqueous solutions by a gas-phase dielectric barrier discharge (DBD) system was investigated. The reactive species generated from the DBD system such as OH • radical, ozone and hydrogen peroxide were measured. The effects of various parameters such as gas flow rate, initial pH, input power, initial concentration of AR88 and the gas source on the degradation of AR88 were studied. The results show that OH • radical was the major reactive species generated when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 39 publications
3
29
0
1
Order By: Relevance
“…However, the half-life time for 60 mg/l is almost 5 times of that for 10 mg/l, which means higher efficiency in case of the higher initial concentration. The behavior of the observed rate constant as a function of the initial concentration was consistent with Tang et al [34] for the degradation of azo dye acid red 88 by dielectric barrier discharge, as well as by Magureanu et al [22] and Gao et al [23].…”
Section: Reaction Order and Kineticssupporting
confidence: 88%
“…However, the half-life time for 60 mg/l is almost 5 times of that for 10 mg/l, which means higher efficiency in case of the higher initial concentration. The behavior of the observed rate constant as a function of the initial concentration was consistent with Tang et al [34] for the degradation of azo dye acid red 88 by dielectric barrier discharge, as well as by Magureanu et al [22] and Gao et al [23].…”
Section: Reaction Order and Kineticssupporting
confidence: 88%
“…The effect of frequency on removal efficiency operated at 20 mL/minute and operating time at 120 minute is displayed in Figure 3a The highest RE with respect to FC was similar to those obtained in previous studies [7,9,18,19]. However, the RE with respect to FC in the present study was higher than that achieved using floating media filter-microfiltration without and with coagulant [18], combination of MBR and chlorination [19], adsorption using a graphite adsorbent with electrochemical regeneration [8,12], and a membrane bioreactor [15]. The REs with respect to FC and TC were quite similar to those using pulsed high voltage [7] and were higher than those using RFICP in a batch experiment and …”
Section: -3supporting
confidence: 87%
“…Previous studies found that active species are produced by plasma (O 3 , H 2 O 2 and  OH) by dissociation of oxygen and water molecules, which can dissolve into the solution and further degrade pollutants via oxidation processes [6,14,15,16]. In another study, the degradation of organic carbon and disinfection of pathogenic bacteria depended on UV light and shock waves produced by plasma discharges [15,16,17].…”
Section: Removal Efficiencymentioning
confidence: 96%
See 1 more Smart Citation
“…Desse modo, os elétrons, que são os principais agentes formadores de espécies quimicamente ativas são gerados em maior quantidade o que aumenta a probabilidade de mais reações por impacto (Cadorni, 2009). Todavia, há um limite no aumento da potência, pois, a produção em excesso de NOx irá também competir com o consumo de átomos de oxigênio, provocando a redução da formação de radicais hidroxila e a redução da quantidade de ozônio disponível no sistema (Tang et al, 2009).…”
Section: Resultsunclassified